Traumas faciais como marcadores de violência física contra idosos - Sousa, Rayanne Izabel Maciel de (2015)
Interpersonal violence is among the main etiological factors of the maxillofacial complex. Trauma, generally, has a great physical impact on older people, because of physical and physiological limitations of age. In view of the importance assumed by physical violence from these lesions in this age range, it was objective of this study evaluate the facial trauma prevalence in older people and factors associated with its occurrence, that do not have caused death, registered at Center for Medicine and Forensic Dentistry (CMFD) of Campina Grande – PB, in the 2008-2010 period.Materials and Methods: Sociodemographic data were analyzed from victims: age range, gender, conjugal status and education; characteristic of aggressors: gender, aggressors and victims relationship and aggression circumstances; aggression circumstances: type of instrument used to perform physical aggression; the shift of occurrence, the weekly period on weekdays and finally the trauma suffered by the victims was grouped into facial trauma and body trauma. Data analysis was done through descriptive and inferential statistical technique. Results: the average age of the victims was 68.44 years (DP = 7.6 years). The proportion of men and woman was 1.5:1. Most elderly people were aged of 60 to 69 years (61.4%), male (60.2%), fixed relationship (58.1%) and had eight years of study or less (85.7%). As the aggressor, the most were male (77.6%) and known to the victim (82.0%). Cases of physical violence against the elderly happened in the community, mainly during morning shift (57.8%) and during working days of the week (67.9%). Most common type of physical violence was through of aggressions without instruments (60.7%). There was facial trauma in 42.9% of the cases. A significate statistical association was found between the presence of facial trauma and age and gender of victim; aggression circumstances, shift of the occurrence, day of the week and used instrument. The Poisson regression analysis for the face trauma occurrence resultant of physical violence against elderly people has proved that no variable included in the model remained significant. The results of multiple correspondence analysis showed that two dimensions explained 34.9% (eigenvalue) of the total viability. It was observed that the variables that most discriminated the dimension 1 were the gender of victim (53.3%), the aggression circumstance (40.0%) and the relationship between aggressor and victim (29.9%). The dimension 2 was composed mainly by used instrument (55.3%), age range of the victim (22.5%) and the type of trauma (19.1%). Conclusion: the presented study evidenced factors associated with facial trauma, enabling the targeting of public health policies in order to prevent and reduce the prevalence of facial trauma resulting from physical violence against the elderly.